Information Security for Automatic Speaker Identification - El-Samie, Fathi E. Abd.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
The author covers the fundamentals of both information and communication security including current developments in some of the most critical areas of automatic speech recognition. Included are topics on speech watermarking, speech encryption, steganography, multilevel security systems comprising speaker identification, real transmission of watermarked or encrypted speech signals, and more. The book is especially useful for information security specialist, government security analysts, speech development professionals, and for individuals involved in the study and research of speech recognition at advanced levels.
1: Fundamentals of Speech Processing -- 2: Chaos Concepts -- 3: Speech Watermarking -- 4: Speech Encryption -- 5. Speech Communication -- 6: Applications in Multi-level Security Systems.
Keywords: Engineering; Telecommunication; Engineering; Signal, Image and Speech Processing; Communications Engineering, Networks